Journey of Gliomas- from Morphology to Genetics: Morphology and Genetics of Gliomas - Chatterjee, Dr Debajyoti (International Journal of Innovative Research in Medical Science, 2018)
Gliomas are the commonest brain tumors, both in adults and children. In the past one decade there is a massive development in the understanding in the pathogenesis and genetics of glial tumors. With the incorporation of the molecular information, gliomas are now classified based both on their morphology and genetics. These changes have been adapted in the current (2016) world health organization (WHO) revised classification of tumors of central nervous system. Incorporation of the molecular information has helped in the accurate classification of glial tumors, which provides important prognostic and predictive information. In this review article, we shall have a brief look at the morphology of the glial tumors with their molecular pathology, in the light of the current literature.